Identification of key miRNAs and target genes in extracellular vesicles derived from low-intensity pulsed ultrasound-treated stem cells - Yin, Xin; Yi, Jialian; Mao, Fugang; Tang, Qisheng; Zhang, Xinyu; Yang, Xiaoyu; Xie, Hongqing; Wang, Linping; Sun, Shuifen; Yu, Xin; Liu, Jie; Jiang, Lihong (Frontiers in Genetics, 2025)
ObjectivesThis study aimed to investigate the impact of low-intensity pulsed ultrasound (LIPUS) treatment on the miRNA and mRNA profiles of stem cell-derived extracellular vesicles (EVs). Specifically, it sought to identify key miRNAs and their target mRNAs associated with enhanced therapeutic efficacy in LIPUS-treated stem cell-derived EVs.MethodsUtilizing miRNA deep-sequencing data from the Gene Expression Omnibus database, differential gene analysis was performed. MiRNA-mRNA target analysis, functional and pathway enrichment analysis, protein-protein interaction network construction, and hub gene identification were conducted. Validation of differentially expressed miRNAs was performed via RT-qPCR in human umbilical cord mesenchymal stem cells (hUC-MSCs) treated with LIPUS.ResultsTen differentially expressed miRNAs were identified, with six upregulated and four downregulated miRNAs in LIPUS-treated stem cell-derived EVs. Functional enrichment analysis revealed involvement in biological processes such as regulation of metabolic processes, cellular component organization, and response to stress, as well as signaling pathways like cell cycle, MAPK signaling, and Hippo signaling. Protein-protein interaction network analysis identified key hub genes including MYC, GAPDH, HSP90AA1, EP300, JUN, PTEN, DAC1, STAT3, HSPA8, and HIF1A associated with LIPUS treatment. RT-qPCR validation confirmed differential expression of selected miRNAs (hsa-miR-933, hsa-miR-3943, hsa-miR-4633-5p, hsa-miR-592, hsa-miR-659-5p, hsa-miR-4766-3p) in LIPUS-treated hUC-MSCs.ConclusionThis study sheds light on the potential therapeutic mechanisms underlying LIPUS-treated stem cell-derived EVs. The identified differentially expressed miRNAs and their potential target mRNAs offer valuable insights into the biological processes influenced by LIPUS treatment. While further investigation is necessary to validate their roles as therapeutic targets, this study lays the groundwork for future research on optimizing SC-EV therapy with LIPUS preconditioning.